Antibiotic resistance profiling of clinical isolates of Salmonella enterica Serovar Paratyphi A in Dhaka, Bangladesh (Stamford Journal of Microbiology, 2021)
The study was conducted to detect the antibiotic resistance profile of the clinical isolates of Salmonella enterica Serovar Paratyphi A from 100 blood samples of patients from different age groups suspected to be suffering from enteric fever. The pure cultures of the bacterial isolates were collected from some renowned diagnostic centers of Dhaka and they were further characterized through the conventional culture, microscopy and biochemical examinations. These isolates were cross checked for the antibiogram profile by the Kirby-Bauer disc diffusion method against ten different types of antibiotics. Most of the isolates were found resistant against azithromycin (100%), nalidixic acid (100%) and ceftazidime (75%). However, isolates showed sensitivity to ciprofloxacin (95%), levofloxacin (97%), cotrimoxazole (96%) and chloramphenicol (95%). These findings highlight the need for continuous monitoring of the drug resistance pattern of S. enterica Serovar Paratyphi A for better public health management.Stamford Journal of Microbiology, Vol.11 (1) 2021: 14-16